Connectivity and local activity within the fronto-posterior brain network in schizophrenia - Sharma, Anuradha; Weisbrod, Matthias; Bender, Stephan (Application of brain oscillations in neuropsychiatric diseases, 2013)
Background: Fronto-posterior networks have been implicated in cognitive control and understanding the detailed functional dynamics within this network is important to understand the pathophysiology of cognitive deficits in schizophrenia. In a previous study (Sharma et al., 2011), we found reduced event-related coherence between frontal and posterior electrode sites in delta and theta frequencies during cognitive control in schizophrenia. The current study aimed to look at the relationship between locally evoked frontal and posterior activity (measured by event-related potentials (ERPs)) and long-range coherence within the fronto-posterior network in healthy controls and patients with schizophrenia. Methods: 16 schizophrenic/schizoaffective patients and 20 age-matched healthy controls performing a choice reaction task took part in the study. We examined ERPs occurring at frontal and posterior sites between 100 and 250ms (overlapping with the time period where coherence deficits were previously found) for differences between patients and controls. ERPs examined were P1a/P2a and N1/N2b components occurring simultaneously during 100-200/200-250ms post stimulus at the frontal (F5′/F6′) and posterior (P7′/P8′) sites, respectively. We further looked at group difference in event-related delta and theta fronto-posterior coherence in the exact same time windows as the ERPs and calculated the correlation between ERP amplitudes and simultaneous event-related delta and theta coherence for both hemispheres and time periods. Bonferroni correction was applied to correct for multiple correlations. Results: We found a significant reduction in schizophrenia patients of the posterior N2b and a trend for reduction for the frontal P2a which are implicated in target-related information processing while the earlier frontal P1a and posterior N1 associated with more general sensory processing were relatively spared. However, the event-related coherence between the frontal and posterior areas was reduced in patients compared to controls during both the early and late time windows, indicating connectivity deficits to be a more consistent impairment in schizophrenia. There was limited linear correlation between fronto-posterior coherence and frontal and posterior ERP amplitudes but uncorrected correlation coefficients showed coherence in delta frequency to be correlated with P2a amplitude in both hemispheres and with P1a only in the left hemisphere in healthy controls. In the patients, however, this correlation was disrupted in the left hemisphere for both early and later stage evoked activity, whereas they showed a similar degree of correlation as healthy controls between P2a and delta coherence in the right hemisphere. Coherence in theta frequency showed no significant correlation with ERPs nor did N1/N2b show any significant correlation with coherence. Conclusions: Impaired cognitive control in schizophrenia might be driven by disrupted communication between the frontal and posterior brain areas, long-range connectivity being a more consistent deficit in schizophrenia as compared to locally evoked activity. Event-related fronto-posterior coherence and locally evoked frontal and posterior ERP amplitudes seem to reflect independent aspects of information processing in the brain although some linear relationship may exist between local frontal activity and fronto-posterior coherence in the delta frequency, implicating this frequency in frontal top-down control of information processing. A disruption of this relationship specifically in the left hemisphere is consistent with previously reported disturbances of the left hemisphere in schizophrenia. Connectivity measures may add important information as markers of cognitive pathophysiology in schizophrenia and may represent a fundamental impairment underlying cognitive control deficits in schizophrenia.